Regulation of APC/C-Cdh1 and Its Function in Neuronal Survival - Almeida, Angeles (Humana Press Inc, 2012)
Neurons are post-mitotic cells that undergo an active downregulation of cell cycle-related proteins to survive. The activity of the anaphase-promoting complex/cyclosome (APC/C), an E3 ubiquitin ligase that regulates cell cycle progression in proliferating cells, plays a relevant role in post-mitotic neurons. Recent advances in the study of the regulation of APC/C have documented that the APC/C-activating cofactor, Cdh1, is essential for the function(s) of APC/C in neuronal survival. Here, we review the normal regulation of APC/C activity in proliferating cells and neurons. We conclude that in neurons the APC/C-Cdh1 complex actively downregulates the stability of the cell cycle protein cyclin B1 and the glycolytic enzyme 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase-3. Keeping these proteins destabilized is critical both for preventing the aberrant reentry of post-mitotic neurons into the cell cycle and for maintaining their reduced antioxidant status. Further understanding of the pathophysiological regulation of these proteins by APC/C-Cdh1 in neurons will be important for the search for novel therapeutic targets against neurodegeneration.